EVALUASI DIMENSI PERABOT PADA RUANG PERPUSTAKAAN UMUM LAMONGAN BERDASARKAN ANTROPOMETRI DAN ERGONOMI - agustapraja, hammam rofiqi; Windarto, Singgih Jiar (Aksen : Journal of Design and Creative Industry, 2021)
The Lamongan public library is one of the public facilities for the Lamongan community which functionsas a medium for distributing information and knowledge to all levels of society. Of these facilities, the mostinfluential are physical facilities such as tables, chairs, bookshelves. Dimensions or physical facilities in alibrary also affect the comfort of its users. Therefore, this study aims to determine whether the dimensionsof the furniture in the Lamongan public library are by the standard with anthropometric and ergonomiccomparisons of visitors. This study uses a quantitative descriptive method, namely by collecting data on thevisitor’s body size, and later it will be compared with the furniture variables used. The results of researchand calculations show that the furniture in the Lamongan public library room, such as chairs, 100% is saidto be feasible, 33.5% type A table is included in the category of not meeting and 66.5% has met, 33.5%type B table is included. The category does not meet and 66.5% has met, for the bookshelf in the libraryroom it can be said to be feasible because it is by anthropometric calculations, suggestions from the resultsof this study are to maintain what is feasible and adjust furniture that is not appropriate to the size of thevisitor’s body.